A Nationwide Cohort Study of Outcome after Pediatric Appendicitis - Omling, Erik; Salö, Martin; Saluja, Saurabh; Bergbrant, Sanna; Olsson, Louise; Björk, Jonas; Hagander, Lars (European Journal of Pediatric Surgery, 2020)
Introduction Children with appendicitis often present with complicated disease. The aim of this study was to describe the clinical management of pediatric appendicitis, and to report how disease severity and operative modality are associated with short- and long-term risks of adverse outcome.Materials and Methods A nationwide retrospective cohort study of all Swedish children (<18 years) diagnosed with appendicitis, 2001 to 2014 (n = 38,939). Primary and secondary outcomes were length of stay, surgical site infections, readmissions, 30-day mortality, and long-term risk of surgery for small bowel obstruction (SBO). Implications of complicated disease and operative modality were assessed with adjustment for age, gender, and trends over time.Results Complicated appendicitis was associated with longer hospital stay (4 vs. 2 days, p < 0.001), increased risk of surgical site infection (5.9 vs. 2.3%, adjusted odds ratio [aOR]: 2.64 [95% confidence interval, CI: 2.18–3.18], p < 0.001), readmission (5.5 vs. 1.2, aOR: 4.74 [95% CI: 4.08–5.53], p < 0.001), as well as long-term risk of surgery for SBO (0.7 vs. 0.2%, adjusted hazard ratio [aHR]: 3.89 [95% CI: 2.61–5.78], p < 0.001). Intended laparoscopic approach was associated with reduced risk of surgical site infections (2.3 vs. 3.1%, aOR: 0.74 [95% CI: 0.62–0.89], p = 0.001), but no overall reduction in risk for SBO; however, successful laparoscopic appendectomy was associated with less SBO during follow-up compared with open appendectomy (aHR: 0.27 [95% CI: 0.11–0.63], p = 0.002).Conclusion Children treated for complicated appendicitis are at risk of substantial short- and long-term morbidities. Fewer surgical site infections were seen after intended laparoscopic appendectomy, compared with open appendectomy, also when converted procedures were accounted for.
Keywords: pediatric appendicitis; complications; surgical site infection; small bowel obstruction; laparoscopic